The effects of Growth Parameters on the Electrical Properties in InAlN/AlN/GaN High-Electron-Mobility Transistors (HEMTs) - Huang, Wei-Ching; Wong, Yuen-Yee; Liu, Kuan-Shin; Hsieh, Chi-Feng; Chang, Edward Yi (My University, 2014)
The electrical properties in the InAlN/AlN/GaN high electron mobility transistor grown by metal-organic vapor deposition (MOCVD) with different growth parameters were investigated in this study. We observed that two-dimensional electron gas (2DEG) channel was influenced by thickness of AlN spacer layer and a stable stage prior to the growth of AlN spacer layer. The TEM images showed the generation of dislocations at interface between AlN/GaN and InAlN/AlN with the thicker AlN spacer layer. These dislocations acted as electron scattering center and degraded the electron mobility in the 2DEG channel. Besides, a too long stable stage also appeared degradation in the electron mobility due to the etching effect of H-2 gas. By optimizing growth parameters, the highest electron mobility of 890 cm(2)/V.s
Keywords: HEMTs; InAlN; GaN; styling; insert